The main directions of scientific-research activity of the department of physics-technical problems of rolling of rolled and special section of the Institute of ferrous metallurgy named after Z.I.Nekrasova of NAN of the Ukraine - S. M. Zhuchkov (Литьë и металлургия, 2002)
/